Securities Market Efficiency During The Announcement Period Of The President And Vice President For The 2024-2025 Period: Abnormal Changes In Return And Trading Volume Activity - David David; Zahroh Naimah (UNIVED Press, 2026)
This study analyzed the impact of the 2024–2029 inauguration of the President and Vice President on the abnormal returns and trading volume activity (TVA) of companies listed on the IDX that comprise the LQ-45 index. This study examines the 20-day interval preceding and succeeding the inauguration date of October 20, 2024, employing an event study methodology. Secondary data sources utilized include stock trading volumes, price summaries, and the Composite Stock Price Index (IHSG). A paired sample t-test is employed for analyzing returns that do not adhere to a normal distribution, while the Wilcoxon signed-rank test is utilized for TVA returns that also deviate from normality. The findings indicate that the incidence of anomalies does not differ considerably before and after the inaugurations of the president and vice president. The inauguration fails to furnish investors with much fresh information, as market expectations were presumably established in advance. Conversely, most LQ-45 companies experienced an increase in stock trading activity following the inauguration, signifying a notable disparity in TVA. The data indicates a substantial increase in trading activity, reflecting heightened investor interest and shifts in investment strategies, but stock prices remained relatively steady. This analysis indicates that the Indonesian capital market is more influenced by certain political events regarding trading volume than by abnormal returns.